1974
DOI: 10.1203/00006450-197401000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Phosphate Isomerase Deficiency with Congenital Nonspherocytic Hemolytic Anemia: A New Variant (Type Nordhorn) I. Clinical and Genetic Studies

Abstract: ExtractA new variant of glucose phosphate isomerase (GPI) deficiency (type Nordhorn) associated with congenital nonspherocytic hemolytic anemia is described. The propositus, an 18-month-old boy of German origin, h,as suffered since birth from a severe to moderate macrocytic anemia, which is characterized by low mean corpuscular hemoglobin concentration (28y0), high reticulocytosis (45-60yo), normal osmotic fragility, type I autohemolysis, and short erythrocyte life-span (51Cr t = 2 days). With the exception of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1974
1974
1997
1997

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…The substrates of this enzyme, fructose-6-phosphate and G6P, are intermediates in glycolysis and gluconeogenesis, as well as intermediates in the pentose phosphate cycle. In humans, GPI deficiency comprises the third most common hereditary enzyme defect of red cells after G6P dehydrogenase deficiency and pyruvate kinase deficiency and has the typical manifestation of nonspherocytic hemolytic anemia (1)(2)(3)(4)(5)(6)(7)(8)(9). It has been reported that severe GPI deficiency can be a cause of hydrops fetalis in humans (10).…”
Section: Introductionmentioning
confidence: 99%
“…The substrates of this enzyme, fructose-6-phosphate and G6P, are intermediates in glycolysis and gluconeogenesis, as well as intermediates in the pentose phosphate cycle. In humans, GPI deficiency comprises the third most common hereditary enzyme defect of red cells after G6P dehydrogenase deficiency and pyruvate kinase deficiency and has the typical manifestation of nonspherocytic hemolytic anemia (1)(2)(3)(4)(5)(6)(7)(8)(9). It has been reported that severe GPI deficiency can be a cause of hydrops fetalis in humans (10).…”
Section: Introductionmentioning
confidence: 99%
“…T h e results obtained with hemolysates of GPI-Nordliorn [8] are different from those of the wild type enLyme: abnormal electroplloretic migration and increased t h e~m a l lability. T h e elevated isoelectric point of 9.80 is in accordance to the electrophoretic study wllicll sllows a migration of 132%.…”
Section: Methodsmentioning
confidence: 79%
“…GPI of case 2 and his parents had already been studied earlier in our laboratory (GPI Nordhorn, SchroÈ ter et al 1974 [25]) but for better comparison some of the data relevant for this study are included in Table 1. Unfortunately the parents of case 2 were not available for the present investigation.…”
Section: Biochemical Characterizationmentioning
confidence: 98%
“…On clinical presentation at the date of gene analysis the patient suered from jaundice with a serum bilirubin level of 7 mg/dl, but no other symptoms. The enzyme variant of case 2 had already been named in a previous publication GPI`Nordhorn' [25].…”
Section: Nomenclaturementioning
confidence: 98%
See 1 more Smart Citation